2016
DOI: 10.1097/tp.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Perioperative Conditions to Prevent Ischemic Cholangiopathy in Donation After Circulatory Death Donor Liver Transplantation

Abstract: Optimizing peritransplant conditions, such as shortening ischemic times with the use of thrombolytic donor flush, may prevent IC after DCD LT. With this approach, the DCD donor pool may be expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 31 publications
3
63
1
Order By: Relevance
“…Also, the Indiana University Group compared cDCD livers treated with TPA added to the aortic flush and subsequently directly injected into the hepatic artery (n = 30) with a historic group of controls from an earlier era (n = 61). They claimed the use of TPA significantly reduced the rates of both anastomotic and nonanastomotic biliary strictures, though donor age was greater and the warm and cold ischemia times significantly longer in non‐TPA grafts . In contrast, a study from Leiden compared recipients of livers treated with urokinase during back‐table surgery (n = 63: 46 DBD and 17 cDCD) with a group of controls from an earlier era (n = 122: 94 DBD and 28 cDCD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the Indiana University Group compared cDCD livers treated with TPA added to the aortic flush and subsequently directly injected into the hepatic artery (n = 30) with a historic group of controls from an earlier era (n = 61). They claimed the use of TPA significantly reduced the rates of both anastomotic and nonanastomotic biliary strictures, though donor age was greater and the warm and cold ischemia times significantly longer in non‐TPA grafts . In contrast, a study from Leiden compared recipients of livers treated with urokinase during back‐table surgery (n = 63: 46 DBD and 17 cDCD) with a group of controls from an earlier era (n = 122: 94 DBD and 28 cDCD).…”
Section: Discussionmentioning
confidence: 99%
“…An additional theory holds that microthrombi deposition in peribiliary arterioles during the low‐flow/no‐flow period following ventilator withdrawal or cardiorespiratory arrest in controlled/expected donation after circulatory death (cDCD) and uncontrolled/unexpected donation after circulatory death (uDCD) donors, respectively, may also play a role. On the basis of this theory, different authors have suggested that the viability of organs arising from DCD donors may be improved through the application of fibrinolytic therapy …”
mentioning
confidence: 99%
“…Successful outcomes have been reported from single centers, with short warm ischemia times, but most US single centers, meta‐analyses, and UNOS data reports demonstrate inferior results with DCD donors, including lower survival and a significant incidence of ischemic cholangiopathy . Although evidence from retrospective series suggests that DCD donor OLT is associated with either equivalent or inferior short‐term and longterm outcomes, recent reports suggest improving outcomes . Khorsandi et al from the UK Institute of Liver Studies, King's College Hospital evaluated survival in patients with HCC undergoing DCD donor or DBD grafts.…”
Section: Dcd Liver Transplantationmentioning
confidence: 99%
“…In particular, the area under the systolic blood pressure curve and slope of the systolic blood pressure regressed from the time of extubation, calculated with the values in the first 10 minutes after extubation, were associated with better outcomes, possibly due to a favorable blood pressure trajectory during the agonal phase. Additionally, once procured, a fibrinolytic preflush such as tissue plasminogen activator (tPA) can be employed to decrease ischemic‐type biliary lesions, which is hypothesized to function by reducing peribiliary microvasculature microthrombi . In an analysis of organ procurement in the Netherlands, it was found that both higher BMI and procurement from a DCD donor were risk factors for increased procurement injury, further suggesting the need for experienced transplant surgeons .…”
Section: Recent Improvements In Dcd Liversmentioning
confidence: 99%
“…While our institution, 2,6 King's, 7 and others 8,9 report outcomes in DCD LT comparable to Donation after Brain Death (DBD), DCD LT is still not perfect. In our report, the incidence of IC and hepatic artery thrombosis in late DCD group was significant high than in DBD group (3 vs. 0.5%, P < .05).…”
Section: Response To "Minimization Of Ischemic Cholangiopathy In Donamentioning
confidence: 99%